An experimental and numerical investigation of clamping force variation in simple bolted and hybrid (bolted-bonded) double lap joints due to applied longitudinal loads. (September 2018) - Esmaeili-Goldarag, F.; Babaei, A.; Jafarzadeh, H.
Abstract: In this research, the variation of clamping force in double lap simple bolted and hybrid (bolted-bonded) joints subjected to longitudinal loads were studied via experimental and FE methods. In order to obtain the initial values of the clamping force as a result of bolt tightening torque in double lap simple bolted and hybrid joints, an experimental method was designed. In another part of the experimental section, the variation of bolt pretension values in both kinds of specimens, under the application of static longitudinal loads were measured. Furthermore, FE simulation was used to analysis the bolt clamping process and obtain the variation of clamping force of bolt in both kinds of the joints, due to longitudinal applied loads. The results of this investigation revealed that in the hybrid joints the clamping force is reduced during tensile longitudinal load application. While in the simple bolted joints the decrease of clamping force in lower longitudinal loads is followed by the latter increase due to further increment of longitudinal load. This can be related to the method that the joint transmits the applied loads. Highlights: The claming force variation in simple and hybrid joints was investigated. In the hybrid joints the clamping force is reduced continuously by applying the tensile load. The clamping force in the simple joints are decreased in the initial stages of applying tensile loads. In the simple specimens, as the tightening torque is increased, a large fraction of the load is transmitted via friction.